Current Challenges in Need of More Stringent Sanctions to Combat Increasing High-tech Crimes in a Developing Country in the Age of Fourth Industrialization - Hoang Do Qui; Tuan Van Vu; Tuan Anh Le (Universitas Negeri Semarang, 2024)
High-tech crime, commonly called cybercrime, is considered a potential threat to individuals, businesses, and governments all over the world. Currently, the fourth industrialization substantially impacts human development, but it also poses many high-tech crimes, which requires a more stringent policy to combat these crimes. This report synthesizes the latest findings on the trends, impacts, and responses to high-tech crimes. The study used the secondary sources of the qualitative method based on the recent approach model of Long-Sutehall et al. (2010), researching, reviewing, generating and synchronizing the common legal frameworks of the legal normative documents, such as Vietnam Criminal Code No. 100/2015/QH13, Law on Cyber Security No. 24/2018/QH14, Budapest Convention (ETS No. 185) and its Protocols, and other legal documentary references. At present, high-tech crime is regarded as a challenge and a new product of human evolution with profoundly negative impacts on each individual, legal entity, country or even the entire community. International cooperation in combating crimes has now shown effectiveness, as there is a lack of a unique legal framework to address this issue. Currently, there has yet to be a unique, effective international law regulating high-tech crimes; consequently, the legal ground, content and modes of international cooperation in combatting this kind of crime exhibit some differences and deliberately require the commitment and goodwill of the subjects on a global scale.